Effect of extract from herbal complex on the clinical and hematological status of white mice - A. A. Ivanovsky; N. A. Latushkina; E. Yu. Timkina (Аграрная наука Евро-Северо-Востока, 2018)
The article provides the results of studies conducted in 2017 on investigating the effect of the herbal extract of herbs (R.carthamoides, S. coronata, F. ulmaria) on the indices of the clinical condition (behavior, blood, internal organs) of non-linear white mice of both sexes with live weight 30 ± 1.0 g at the age of 3 months. The animals were divided into one control and three experimental groups of 15 mice each. The phytoextract dissolved in physiological solution was administered orally daily to the mice of the experimental groups for 7 days in doses: the first group 0.1 ml (0.65 mg of extractive substances), the second group 0.3 ml (1.95 mg) and the third group 0.5 ml (3.25 mg). In control - physiological solution in a dose of 0.5 ml. During the experiment, the general condition of the animals was observed. Before and after the experiment, the mice were weighed. When the experiment was completed, the mice were taken blood for a number of morphological and biochemical studies, including characterizing and antioxidant status. The effect of internal organs (liver, kidneys, spleen) on the mass was evaluated. The results of blood tests showed that in mice of the second experimental group, the number of erythrocytes in comparison with the control (4.2 x1012 kl / l) increased by 45% (6.1 x 1012kl / l), hemoglobin - by 6% (from 112 up to 119 g / l); total protein in serum by 7% (from 61.2 to 65.5 g / l), albumin - by 4% (from 73.5 to 76.5%), SH-group of proteins - by 54% (from 2,2 to 3.4 mmol / l), а-globulins decreased by 39% (from 14.2 to 8.7%), malonic dialdehyde - by 45% (from 6.3 to 3.5 μmol / l) ( P 0.05) differences and was within the regulatory limits.